Evaluating the relationship between right-to-left shunt and white matter hyperintensities in migraine patients: A systematic review and meta-analysis - Yeo, Joshua Y. P.; Goh, Claire X. Y.; Tan, Ying Kiat; Sim, Bryan T. S.; Chan, Beverly L. X.; Syn, Nicholas L.; Lim, Yinghao; Chan, Amanda C. Y.; Sharma, Vijay K.; Ong, Jonathan J. Y.; Yeo, Leonard L. L.; Sia, Ching-Hui; et al. (Frontiers in Neurology, 2022)
Introduction White matter hyperintensities (WMHs) have been observed with greater frequency in patients with migraine and are thought to be associated with impaired cognition and function. The relationship between WMHs and right-to-left shunt (RLS) in migraine patients is unknown. We performed a systematic review to determine if there is an association between RLS and WMHs in patients with migraine. Methods A systematic search of the literature was performed in PubMed and Embase using a suitable keyword search strategy from inception up to 16th June 2021. All studies that included patients with migraine and studied RLS and WMHs were included. Results A total of 8 non-randomized observational studies comprising 1125 patients with migraine were included; 576 had an RLS, compared to 549 patients with no RLS. The mean age of the study populations ranged from 28.4–43 years, while the average duration from migraine diagnosis ranged from 5.1–19 years. The proportion of female to male patients was consistently higher in all studies (60.0%–94.4%). Amongst migraine patients with RLS, 338 patients (58.7%) had WMHs. In contrast, 256 (46.6%) of migraine patients without RLS had WMHs. RLS was significantly associated with the presence of WMHs in migraine patients (OR: 1.56, 95% CI: 1.05-2.34, p = 0.03). Conclusion In migraine patients, RLS was significantly associated with the presence of WMHs. Longitudinal studies are warranted to establish RLS as a risk factor for WMHs in patients with migraine, and to establish the significance of these changes.